Probiotics combined with prebiotics alleviated seasonal allergic rhinitis by altering the composition and metabolic function of intestinal microbiota: a prospective, randomized, double-blind, placebo-controlled clinical trial - Hou, Yangfan; Wang, Dan; Zhou, Shuru; Huo, Caifang; Chen, Haijuan; Li, Fangxia; Ding, Minjuan; Li, Hongxin; Zhao, Hongyan; He, Jin; Da, Hongju; Ma, Yu; et al. (Frontiers in Immunology, 2024)
Background: Numerous studies have established that probiotics or prebiotics can relieve the symptoms of allergic rhinitis (AR), but their mechanism of action remain underexplored. This study aimed to observe the clinical efficacy of probiotics combined with prebiotics in seasonal AR patients and explore their underlying mechanisms. Methods: We conducted a prospective, randomized, double-blind, placebo-controlled clinical trial. The test group was given probiotics combined with prebiotics, whereas the placebo group was administered simulated preparation for 90 days. Outcome measures included total nasal symptom score (TNSS), visual analog scale, rhinitis quality of life questionnaire, fractional exhaled nitric oxide, and the rate and intensity of Loratadine use. Serum TNF-α, INF-γ, IL-4, IL-17, and IgE levels were measured by enzyme-linked immunosorbent assay. Intestinal microbiota was detected by 16S rRNA gene sequencing and quantitative PCR. Short-chain fatty acids were analyzed by gas chromatography-mass spectrometry. Results: 106 participants (N = 53 for both test group and placebo group) completed the study. From baseline to day 91, mean difference between groups (MDBG) in the reduction of TNSS was -1.1 (-2.2, -0.1) (P = 0.04); MDBG in the increment of TNF-α was 7.1 pg/ml (95% CI: 0.8, 13.4, P = 0.03); the INF-γ level was significantly increased (P = 0.01), whereas that of IL-17 (P = 0.005) was significantly decreased in the test group, whilst mean difference within groups was not statistically significant in the placebo group; MDBG in the increment of acetate was 12.4% (95% CI: 7.1%, 17.6%, P <0.001). After the administration of probiotics and prebiotics, the composition and metabolic function of the intestinal microbiota were significantly altered and positively related to the beneficial effect on seasonal AR patients. Conclusion: Probiotics combined with prebiotics administered for 90 days significantly attenuated the symptoms of seasonal AR patients, which may related to fluctuations in the composition and metabolic function of the intestinal microbiota and further ameliorating host immunity.